A Three-Dimensional Alzheimer’s Disease Cell Culture Model Using iPSC-Derived Neurons Carrying A246E Mutation in PSEN1 - Hernández-Sapiéns, Mercedes A.; Reza-Zaldívar, Edwin E.; Cevallos, Ricardo R.; Márquez-Aguirre, Ana L.; Gazarian, Karlen; Canales-Aguirre, Alejandro A. (Frontiers in Cellular Neuroscience, 2020)
Alzheimer’s disease (AD) is a chronic brain disorder characterized by progressive intellectual decline, memory and neuronal loss, caused mainly by extracellular deposition of amyloid-beta (Aβ) and intracellular accumulation of hyperphosphorylated tau protein, primarily in areas implicated in memory and learning as prefrontal cortex and hippocampus. There are two forms of AD, a late-onset form that affects people over 65 years old, and the early-onset, which is hereditable and affect people at early ages ~45 years. To date, there is no cure for the disease; consequently, it is essential to develop new tools for the study of processes implicated in the disease. Currently, in vitro AD three-dimensional (3D) models using induced Pluripotent Stem Cells (iPSC)-derived neurons have broadened the horizon for in vitro disease modeling and gained interest for mechanistic studies and preclinical drug discovery due to their potential advantages in providing a better physiologically relevant information and more predictive data for in vivo tests. Therefore, this study aimed to establish a 3D cell culture model of AD in vitro using iPSCs carrying the A246E mutation. We generated human iPSCs from fibroblasts from a patient with AD harboring A246E mutation in the PSEN1 gene. Cell reprogramming was performed using lentiviral vectors with Yamanaka’s factors (OSKM: Oct4, Sox2, Klf4, and c-Myc). The resulting iPSCs expressed pluripotency genes (such as Nanog and Oct4), alkaline phosphatase activity, and pluripotency stem cell markers expression, such as OCT4, SOX2, TRA-1-60, and SSEA4. iPSCs exhibited the ability to differentiate into neuronal lineage in a 3D environment through Dual SMAD inhibition as confirmed by Nestin, MAP2, and Tuj1 neural markers expression. These iPSC-derived neurons harbored Aβ oligomers confirmed by Western Blot and immunostaining. With human iPSC-derived neurons able to produce Aβ oligomers, we established a novel human hydrogel-based 3D cell culture model that recapitulates Aβ aggregation without the need for mutation induction or synthetic Aβ exposure. These model will allow the study of processes implicated in disease spread throughout the brain, the screening of molecules or compounds with therapeutic potential, and the development of personalized therapeutic strategies.